Public electric vehicle charging station utilization in the United States. (January 2023) - Borlaug, Brennan; Yang, Fan; Pritchard, Ewan; Wood, Eric; Gonder, Jeff
Abstract: The utilization of electric vehicle (EV) charging equipment is a key driver of charging station economics, but current trends and factors related to the utilization of public charging infrastructure in the United States are not well understood. This study analyzes EV charging data from 3, 705 nationwide public Level 2 (L2) and direct current fast charging (DCFC) stations over 2.5 years (2019–2022), observing utilization patterns over time. Regression analysis is used to assess the relationships between station utilization and several contextual and environmental factors. We conclude that local EV adoption is a strong indicator of utilization; L2 station utilization decreases with the size of the local charging network, while DCFC stations are less affected; and increased charging power has a greater effect on utilization for DCFC stations than L2. This study fills a critical research gap by reporting updated public charging station utilization statistics and analysis for the U.S. market.